The Value of Contemporary Legal and Institutional Tools of Inquiry of Truth in the Marriage Nullity Process: Following “the Hermeneutic of Renewal in Continuity” - PASTWA, ANDRZEJ (Prawo Kanoniczne, 2012)
There are two main inspirations for this paper: the formula expressed in the subtitle, which was used by the Pope Benedict XVI in his address to the Rota Romana on the 27th of January 2007; and an important quote from John Paul II’s speech to the Rota (2005): „The judge must then abide by canonical laws,correctly interpreted. Hence, he must never lose sight of the intrinsic connection of juridical norms with Church doctrine”. In this doctrinal context it is suitable and fruitful to inquire into the following issues: in the first part – the normative gravity of the Instruction Dignitas connubii, in the second – the value of judicature of the Tribunal of the Rota Romana, in the third – the legal importance of the popes’ addresses to this Tribunal.